Multi-criteria supplier evaluation and selection using fuzzy AHP (alpha cut analysis): a case study. (8th August 2011) - Arunkumar, N.; Karunamoorthy, L.; Muthukumar, S.
In today's competitive environment, an effective supplier selection process has a significant place in the success of manufacturing companies. Selecting the right suppliers help to reduce the purchasing cost and increase the competitiveness of the company. An analytical way to reach the best decision is more preferable in many business platforms. Analytical hierarchy process (AHP) is one of the best ways for deciding among the complex criteria structure in different levels. In this paper, a new method is presented to deal with the performance evaluation and selection of supplier for a manufacturing industry using fuzzy alpha cut analysis. It suggests the use of triangular fuzzy number to express the subjective preferences of evaluators. A usability evaluation of the AHP-based model with seven suppliers is discussed and a hypothetical supplier selection problem is solved. Fuzzy analytical hierarchy process (FAHP) is a new multi-criteria evaluation method evolved from Saaty's AHP when there is fuzziness in the decision making. The results of this paper provide valuable suggestions to managers on the improvement needed with respect to each criterion when selecting suppliers.